IMPLEMENTATION OF RESTORATIVE JUSTICE IN THE CRIMINAL SYSTEM IN INDONESIA - Subroto, Mitro; Rovindra, Najla Putra (Universitas Nusa Cendana, 2025)
This study was written to identify the types of restorative justice and to determine whether this approach can be applied in Indonesia. This research utilizes the literature review method. The literature review has several characteristics. First, this research deals directly with textual and numerical data, not with events or witnesses in the form of incidents, people, or other objects. Second, the data has already been compiled, so the researcher only needs to work directly with the sources available in the library. Third, library data is generally a secondary data source. Restorative justice is a judicial process that prioritizes compensation for losses caused by criminal acts. There are various types of restorative justice practices. The suitable restorative justice approach for use in Indonesia is victim-offender mediation, which has been implemented in the juvenile criminal justice system as regulated by Law No. 11 of 2012. The implementation of restorative justice in Indonesia requires public awareness and understanding. This approach is suitable for Indonesia, specifically through victim-offender mediation, which has been carried out in the juvenile criminal justice system as stipulated in Law No. 11 of 2012. In the future, restorative justice in Indonesia can be applied to criminal acts with a penalty of no more than 5 years, offenses that do not endanger human life, and crimes that do not degrade human dignity. Keywords: Application; Restorative Justice; Criminal